ANALYSIS OF THE ROLE OF WOMEN IN AGRICULTURE IN LAWE ALAS DISTRICT, SOUTHEAST ACEH REGENCY - Zeni Abdi (Jurnal Penelitian Progresif, 2026)
The separation of work based on gender has eroded over the course of human civilization, including in the agricultural sector. This study involved 50 respondents from 237 complete couples who owned at least 0.5 hectares of land. The study examined and analyzed women's contributions to the agricultural economy in the Lawe Alas subdistrict of Southeast Aceh, beyond their roles as housewives. Women's roles in the agricultural economy are divided into two activities: first, pre-harvest activities such as soil cultivation, seed or fertilizer preparation, weeding, pest and disease prevention, and watering; and second, harvesting and post-harvest activities such as seed separation, harvesting, cleaning, transportation, sorting, and marketing. On average, women in Lawe Alas Subdistrict, Southeast Aceh Regency, spend 5.3 hours per day engaged in agricultural activities on an average land area of 1.26 hectares, which is equivalent to 2.6 workers per working day/5 hours. Women's contribution to the agricultural economy in Lawe Alas sub-district, Southeast Aceh district, is 49.69% in land preparation, 53% in seed/fertilizer preparation, and 52.22% in planting for each pre-harvest activity, 52.22% in fertilization, 51.53% in weeding, and 54.25% in watering. Women's contribution to the agricultural economy in Lawe Alas subdistrict, Southeast Aceh district, in each harvesting and post-harvesting activity is as follows: 50.25% in threshing, 66.25% in harvesting, 33.13% in transportation, 55.22% in cleaning, 52.97% in sorting, and 53.00% in marketing. Women in the agricultural economy in Lawe Alas subdistrict, Southeast Aceh district, have a large contribution in almost all pre-harvest, harvest, and post-harvest activities, but they have a small contribution in decision-making regarding the selection of crop varieties (28%), planting schedules (32%), seeds, and fertilizers for planting and fertilization.